Academic analytics: anatomy of an exploratory essay - Ferreira, Sérgio André (2014)
Investment in technological subsystems to support the activity of teaching and learning and the various areas of the life of Higher Education Institutions (HEI) is of increasing importance in the implementation of the policy and strategy of these organizations. Each of these subsystems collects a huge amount of data that, if properly organized, can provide useful information for decision making and informed action, which results in the need to articulate the strategic vision with Information Systems. This study aims to identify the technological requirements and understand the technical difficulties in accessing data sources of different technological subsystems in order to facilitate dialogue between the departments which hold the data to build a future Academic Analytics in a HEI. To achieve these goals a prototype was conceived which involved the aggregation, cleansing and standardization of data sources and resulted in a database that integrates records from three data sources—the LCMS (Learning Content Management System), academic management services and quality management services. This prototype allows reports and analysis to be made. Future studies for the development and implementation of Academic Analytics that can produce information to support decision making and control of the HEI’s activity are also possible.